2021
DOI: 10.1021/acs.iecr.1c01054
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Experimental Study of Mass Transfer Properties of Micronanobubbles

Abstract: In order to study the mass transfer efficiency of micronanobubbles (MNBs), an equation of the volumetric mass transfer coefficient (k L a) was proposed based on theory and dimensionless numbers. It was verified by experimental data from different literature sources. Then, the k L a in an MNB column was measured under the conditions of different salt concentrations. The test results showed that the equation could successfully predict the k L a in an MNB column of not only this research but also other literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Pressurized dissolution type MNB generator (XZCP-K-1.1, Yunnan Xiazhichun Environmental Protection Technology Co., Ltd, China) was used for MNB aeration. The method of MNB aeration was described in previous literature (Bai et al, 2021). CB was generated by the tube with a diameter of 3 mm.…”
Section: Experiments Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pressurized dissolution type MNB generator (XZCP-K-1.1, Yunnan Xiazhichun Environmental Protection Technology Co., Ltd, China) was used for MNB aeration. The method of MNB aeration was described in previous literature (Bai et al, 2021). CB was generated by the tube with a diameter of 3 mm.…”
Section: Experiments Methodsmentioning
confidence: 99%
“…The fast increase rate of DO, the great DO peak value and the higher oxygen utilization e ciency in groundwater during MNB aeration resulted from high mass transfer e ciency of MNB. In order to investigate the mass transfer e ciency of MNB and CB aeration, the volumetric oxygen transfer coe cient (k L a) of MNB and CB were calculated by the following equation (Bai et al, 2021):…”
Section: Contaminant Removal E Ciencymentioning
confidence: 99%
See 1 more Smart Citation
“…During the MNB aeration, 20 L contaminated groundwater was fed into the bubble column, and the oxygen flow rate was controlled at 1.8 L min −1 . 29 The DO concentration of groundwater was recorded using a DO meter (YSI ProSolo). The DO meter read the value every second.…”
Section: Methodsmentioning
confidence: 99%
“…The high DO peak value indicated that MNB aeration effectively increased the DO concentration of groundwater. To assess the oxygen mass transfer efficiency of the oxygen MNB aeration, the oxygen volumetric transfer coefficient (k L a) was calculated by the following equation: 29 dC* dt…”
Section: Mass Transfer In Mnb Aerationmentioning
confidence: 99%